Perencanaan Sistem Drainase Perumahan Cendana Marq - Tangerang - Irsanti; Mardiaman; Sampurna Bangun (Jurnal Rekayasa Teknik Sipil dan Lingkungan - CENTECH, 2024)
PT. Darma Sarana Nusa Pratama established the drainage system for the Cendana Marq housing complex in Tangerang. This drainage system was built on previously agricultural land, which has undergone a change in function to residential use. Consequently, the infiltration capacity of rainwater on this land has altered, affecting the volume of runoff directed towards the drainage system. The objectives of this research include planning the drainagesystem for the Cendana Marq housing complex in Curug, Tangerang. This involves designing the drainage network, determining the amount of rainwater runoff, calculating the necessary dimensions for the drainage channels to accommodate the runoff, assessing the required capacity for a retention pond intended for temporary water storage, and identifying the necessary drainage facilities for the Cendana Marq housing system. The study employs a qualitative research methodology. The findings indicate that the dimensions of the tertiary channels range from 0.40 to 0.55 meters, secondary channels from 0.80 to 1.40 meters, and primary channels at 1.50 meters, all leading to a retention pond. The runoff volume generated by the housing development is calculated to be 1.45 m³/s, which will be temporarily held in the retention pond within the residential area. To enable gravity flow, the required embankment height for the Cendana Marq housing complex is 2.10 meters (+7.302) above the village road (+5.402). Prior to the establishment of the housing complex, the river did not overflow during rainfall, with water levels matching the height of the embankment. The inflow to the Afvoer Cantel from the watershed area before the housing development was 0.28 m³/s. The planned drainage system for the Cendana Marq housing complex will manage rainwater runoff through the retention pond and designated channels, allowing for gravity drainage. Thus, the CendanaMarq housing complex in Tangerang is not expected to adversely impact the capacity of the system.